Long-term observation of adsorbed heavy metal ions in sediment samples by MRI - Nestle, Nikolaus; Ebert, Martin; Wunderlich, Arthur; Baumann, Thomas (Diffusion Fundamentals, 2007)
Recently, we have reported studies of transport and sorption of heavy metal ions in water-saturated quartz sand columns under relatively fast water flow. In these experiments, clear indications for a fast and strong adsorption of the ions to the sediment could be found. Here we report the findings in a series of other experiments performed under static conditions. In this case, much higher concentrations of ions are adsorbed to the sand and remain immobile over time scales of more than a year. Changes in the MRI contrast observed for the sediment areas with the adsorbed ions indicate rearrangements in the distribution of the ions during the first days after administration to the sediment. EDX-studies of the ion distribution after several days indicate a spatially inhomogeneous distribution of adsorbed ions on the surface of the quartz sand. If the adsorbed ions are subjected to flow, a part of adsorbed ions moves away with the water flow. Also all ions are rapidly accessible to acid leaching.